Superformula

From Wikipedia, the free encyclopedia
  (Redirected from Johan Gielis)
Jump to: navigation, search
Some superformula samples: a=b=1; m, n1, n2 and n3 are shown in picture.

The superformula is a generalization of the superellipse and was first proposed by Johan Gielis.

Gielis suggested that the formula can be used to describe many complex shapes and curves that are found in nature.

In polar coordinates, with r the radius and \varphi the angle, the superformula is:

r\left(\varphi\right) =
\left[
        \left|
                \frac{\cos\left(\frac{m\varphi}{4}\right)}{a}
        \right| ^{n_{2}}
+
        \left|
                \frac{\sin\left(\frac{m\varphi}{4}\right)}{b}
        \right| ^{n_{3}}
\right] ^{-\frac{1}{n_{1}}}

The formula appeared in a work by Gielis. It was obtained by generalizing the superellipse, named and popularized by Piet Hein, a Danish mathematician.

Extension to higher dimensions[edit]

It is possible to extend the formula to 3, 4, or n dimensions, by means of the spherical product of superformulas. For example, the 3D parametric surface is obtained by multiplying two superformulas r1 and r2. The coordinates are defined by the relations:

 x \,=\, r_1(\theta)\cos(\theta)r_2(\phi)\cos(\phi)
 y \,=\, r_1(\theta)\sin(\theta)r_2(\phi)\cos(\phi)
 z \,=\, r_2(\phi)\sin(\phi)

where \phi varies between -π/2 and π/2 (latitude) and θ between and π (longitude).

Plots[edit]

Sf2d.png

A GNU Octave program for generating these figures:

  function sf2d(n,a)
    u=[0:.001:2*pi];
    raux=abs(1/a(1).*abs(cos(n(1)*u/4))).^n(3)+abs(1/a(2).*abs(sin(n(1)*u/4))).^n(4);
    r=abs(raux).^(-1/n(2));
    x=r.*cos(u);
    y=r.*sin(u);
    plot(x,y);
  end




3d Superformula: a=b=1; m, n1, n2 and n3 are shown in the pictures.

A GNU Octave program for generating these figures:

 function sf3d(n, a)
  u=[-pi:.05:pi];
  v=[-pi/2:.05:pi/2];
  nu=length(u);
  nv=length(v);
    for i=1:nu
    for j=1:nv
      raux1=abs(1/a(1)*abs(cos(n(1).*u(i)/4))).^n(3)+abs(1/a(2)*abs(sin(n(1)*u(i)/4))).^n(4);
      r1=abs(raux1).^(-1/n(2));
      raux2=abs(1/a(1)*abs(cos(n(1)*v(j)/4))).^n(3)+abs(1/a(2)*abs(sin(n(1)*v(j)/4))).^n(4);
      r2=abs(raux2).^(-1/n(2));
      x(i,j)=r1*cos(u(i))*r2*cos(v(j));
      y(i,j)=r1*sin(u(i))*r2*cos(v(j));
      z(i,j)=r2*sin(v(j));
    endfor;
  endfor;
  mesh(x,y,z);
 endfunction;

References[edit]

External links[edit]